Wind tunnel study of stack gas dispersal at Harrington Power Station - Cermak, Jack E., author; Meroney, Robert N., author; Fluid Dynamics and Diffusion Laboratory, Department of Civil Engineering, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1976)
Tests were conducted in the Colorado State University Meteorological Wind Tunnel facility, to study the gaseous plumes released from stacks associated with the Harrington Power Station of the Southwestern Public Service Company. The tests were conducted over a model power plant to scale 1/250 including all significant structures, topography, and roughness elements in the vicinity. Effects of wind orientation, stack height, plant operation load, and wind velocity were established. Data obtained included photographs and color motion pictures of smoke plume trajectories and contaminant concentration downwind of the power plant at ground level sampling positions.
April 1976.
CER75-76RNM-JEC24.
Keywords: Amarillo (Tex.) -- Buildings, structures, etc.; Wind tunnel models; Buildings -- Aerodynamics; Smoke plumes